Gene regulatory networks governing the generation and regeneration of blood - Ciau-Uitz, A; Patient, R (Mary Ann Liebert, 2019)
Blood is an example of a highly regenerative tissue and its regeneration depends on the presence of stem cells residing in the bone marrow in humans. A better understanding of how these stem cells are programmed would benefit their use in clinical practice and shed light on the mechanisms by which the unique properties of stem cells are established. Our approach is to delineate the gene regulatory networks (GRNs) that specify these cells during their development in the embryo, and we use the amphibian experimental model because a wealth of evidence shows that the mechanisms used are conserved in mammals including humans. Blood stem cells are made during the intraembryonic wave of hematopoiesis during embryonic development where they emerge from endothelial precursors in the floor of the dorsal aorta (DA). These cells are derived from lateral plate mesoderm and so we have focused on the subset of cells in the lateral plate mesoderm fated to become blood and endothelium known as definitive hemangioblasts. We have found that their programming results from the activities of vascular endothelial growth factor A (VEGFA) and bone morphogenetic protein (BMP) signaling and the inhibition by miRNA of transforming growth factor beta signaling. VEGFA is first generated in the somites adjacent to the lateral plate mesoderm, and one of the responses of the lateral plate mesoderm is to activate endogenous VEGFA expression. BMP has multiple inputs into the programming of these cells via the activation of the transcription factor (TF), Gata2, and of the VEGFA receptor. These actions culminate in the expression of the leukemia-associated TF, Scl/Tal1, which is essential for blood fate specification. The activity of VEGFA in driving endothelial development resides in the small isoform, but the medium and large isoforms are required to initiate the blood stem cell program in the floor of the DA. The expression of the small isoform is dependent on the blood TF with leukemia connections, Tel1/Etv6, whereas the larger isoforms depend on another transcription-associated factor with leukemia connections, Eto2, raising the possibility that the regulation of VEGFA expression may be the mode of action of these leukemic factors. The action of Tel1/Etv6 in directly activating VEGFA expression in the somites was unexpected because this TF had only been reported to repress transcription. Using chromatin immunoprecipitation technology, we were able to show that Tel1/Etv6 does indeed work by repressing the expression of a VEGFA repressor, FoxC3, but it also acts directly to activate VEGFA expression, working together with Klf4. Finally, we have also looked at the mesodermal population that gives rise to the earlier waves of hematopoiesis, which do not generate a stem cell. We find significant differences including differential use of TFs of the E-Twenty-Six (ETS) family. In conclusion, we have elucidated the GRN responsible for preparing the lateral mesoderm for blood stem cell production.